Association between postoperative atrial fibrillation after coronary artery bypass grafting and short-term clinical outcomes - Youn-Jung Son; Hong-Jae Choi; JaeLan Shim (BMC Cardiovascular Disorders)
Abstract Background Despite advances in prevention and treatment, postoperative atrial fibrillation (POAF) is the most common type of complication undergoing cardiac surgery. This study aimed to identify the relationship between POAF and clinical outcomes after coronary artery bypass graft. Methods In this cross-sectional study, we retrospectively reviewed the medical records of 324 patients who had undergone coronary artery bypass grafting in an intensive care unit between 2010 and 2019 at a tertiary hospital in Korea. Propensity score matching was used to estimate a 1:1 match (without: with POAF) using seven covariates to overcome selection bias. Kaplan–Meier survival analysis and Cox proportional hazards modeling were performed to determine the effect on intensive care unit readmission and length of hospital stay. Results After controlling for covariates, 1:1 matching was performed for 91 patients in each group. The occurrence of postoperative atrial fibrillation was found to increase the probability of readmission to the intensive care unit, with a 23% reduced probability of readmission for every 10% increase in left ventricular ejection fraction. Multivariate analysis indicated that postoperative atrial fibrillation, chronic obstructive pulmonary disease as a comorbidity, and preoperative hemoglobin were factors affecting the length of hospitalization after surgery. The Kaplan–Meier survival analysis results indicated that the without POAF group had a higher survival rate than the with POAF group. Conclusions Healthcare professionals should recognize negative factors such as postoperative atrial fibrillation and abnormal hematologic parameters that impact major clinical outcomes in patients and may require closer monitoring before and after coronary artery bypass grafting.